1-D wave-like chain, twofold 2-D layer, and chiral 3-D open framework based on multidentate ligand: structural diversities, thermal properties, and photoluminescence. Issue 6 (18th March 2016) - Zhang, Hui-Jie; Wang, Ping; Fan, Rui-Qing; Dong, Yu-Wei; Wang, Xin-Ming; Song, Yang; Wang, Yu-Lei; Yang, Yu-Lin
Abstract: From 1-D to 3-D zinc coordination polymers based on multifunctional flexible 4-(1, 2, 4-triazole-methylene)-benzonitrile (tzbt), {[Zn(tzbt)2 (bdc)]·2H2 O}n (1 ), [Zn(tzbc)2 ]n (2 ), and [Zn(bpdc)(H2 O)]n (3 ) (bdc = 1, 4-benzenedicarboxylic acid, tzbc = 4-(1, 2, 4-triazole-methylene)-benzoic acid, bpdc = 4, 4′-biphenyldicarboxylic acid), were synthesized under hydrothermal conditions. The tzbt was synthesized by N -alkylation and hydrolyzed in situ to produce tzbc (in2 ). Single-crystal X-ray diffraction analysis reveals that1 displays 1-D wave-like chains based on [Zn(bdc)]n .2 is a chiral twofold interpenetrating 2-D architecture constructed with "V"-shaped tzbc.3 is a 3-D chiral compound constructed from achiral H2 bpdc with right-handed helical chains.1–3 display stable blue-emitting luminescence with emission maxima ranging from 383 to 410 nm, depending on ligand-centered π *→ π transitions. The effects of different polarity solvents and temperature on luminescence are discussed. TGA and VT-XPRD reveal that2 has thermal stability to 360 °C. Abstract :